Sarcopenic obesity: epidemiology, pathophysiology, cardiovascular disease, mortality, and management - Wei, Shibo; Nguyen, Thanh T.; Zhang, Yan; Ryu, Dongryeol; Gariani, Karim (Frontiers in Endocrinology, 2023)
Sarcopenic obesity is defined as the coexistence of sarcopenia and obesity in the same individual, characterized by of the co-presence of body fat accumulation and muscle loss. This condition is currently a major concern as it is associated with frailty and disabilities such as cardiovascular disease, fractures, dementia, cancer, and increased all-cause mortality. Particularly, older individuals remain at risk of sarcopenic obesity. Progress at several levels is needed to improve the global prognostic outlook for this condition, including the elaboration and implementation of a more uniform definition that may favor the identification and specification of prevalence by age group. Furthermore, improvements in the understanding of the pathogenesis of sarcopenic obesity may lead to the development of more specific therapeutic interventions to improve prognosis. We reviewed the knowledge on sarcopenic obesity and its associations with cardiovascular diseases and mortality.